Prevalence of anemia and consumption of iron-rich food groups in Mexican children and adolescents: Ensanut MC 2016 - Vanessa De la Cruz-Góngora; Salvador Villalpando; Teresa Shamah-Levy (Instituto Nacional de Salud Pública, 2018)
Objective. To describe the prevalence of anemia and consumption of iron rich groups among Mexican children and adolescents who participated in the Halfway National Health and Nutrition Survey, 2016. Materials and methods. Our study sample included children and adolescents who provided full capillary hemoglobin data. Anemia was defined according to WHO criteria. Logistic regression models were used to explore the association among consumption of iron-rich food groups, sociodemographic characteristics and anemia. Results. In 2016, the prevalence of anemia was 26.9% in children aged 1 to 4 years old, 12.5% in those aged 5 to 11, and 9.6% in adolescents aged 12 to 19 years. Rates were the highest among females who lived in the southern and central parts of Mexico, belonged to an indigenous ethnic group and fell within the first tercile of the Household Wealth Index. Consumption of beef by preschoolers and viscera by adolescents was associated with lower risk for anemia; higher risk was associated with consumption of Liconsa milk and non-heme iron by preschoolers. Conclusions. Anemia is highly prevalent in Mexican children and adolescents, affecting mainly the poorest and youngest populations. Sources of heme iron are the principal dietary factor associated with low risk for anemia.